A Sensitive and Optimized HPLC-FLD Method for the Simultaneous Quantification of Hydroxychloroquine and Its Two Metabolites in Blood of Systemic Lupus Erythematosus Patients. (1st June 2020) - Luo, Xuemei; Peng, Ying; Ge, Weihong
Abstract: Quantification of hydroxychloroquine (HCQ) and its two metabolites desethylchloroquine and desethylhydroxychloroquine in human blood can provide insight into the pharmacokinetic/pharmacodynamic characteristics of HCQ for the treatment of systemic lupus erythematosus (SLE), which is crucial for the optimization of the therapy. A simple, sensitive and optimized high performance liquid chromatography with fluorescence detection method has been developed and validated for the simultaneous determination of HCQ and its two metabolites in human blood. After addition of internal standard chloroquine, the blood sample was deproteinized with 2-fold acetonitrile and separated on an YMC-Triart C18 column (250 × 4.6 mm, 5 μm) with a mobile phase of 20 mM sodium phosphate buffer solution containing 0.25% triethylamine (pH 8.0)—acetonitrile (60:40, v/v). The analytes were detected by using fluorescence detection at an excitation and emission wavelength of 337 and 405 nm, respectively. The method was linear over the range of 3–3000 ng/mL for all three analytes and the chromatographic run time was 9 min. The values for intra- and inter-day precisions were ranged from 1.3 to 7.3. This method was successfully applied to quantify the concentrations of HCQ and its two metabolites in blood of 92 SLE patients.